Charting Sustainable Tourism Futures: A Comprehensive Analysis of Challenges and Strategies for Lombok, Indonesia - Supiandi, Supiandi (Advances in Tourism Studies, 2023)
As global tourism burgeons, destinations like Lombok, Indonesia, grapple with the imperative of sustainable development to balance economic growth with environmental and cultural preservation. This research navigates the multifaceted challenges and opportunities facing Lombok's tourism future, employing a dual-method approach of literature review and stakeholder interviews. The results unveil key challenges, including infrastructure deficiencies, environmental vulnerabilities, cultural dilution risks, community disparities, natural disaster susceptibility, and regulatory inadequacies. Drawing on insights from past research, the discussion elucidates sustainable strategies tailored to Lombok's context. Infrastructure development emerges as a linchpin for enhancing tourism appeal, while environmental sustainability, cultural preservation, and community involvement strategies harmonize with global lessons. Natural disaster preparedness and regulatory frameworks find resonance in analogous destinations, offering Lombok a blueprint for resilience and responsible growth. The implications extend beyond Lombok, contributing a model for sustainable tourism development that integrates theory with practical insights, guiding stakeholders worldwide. This research illuminates a trajectory towards a future where the enchantment of Lombok is preserved and flourishes harmoniously in the dynamic and responsible milieu of global tourism.